Design, synthesis and photophysical aspects of 1, 2, 3-triazole appended Schiff base functionalized silanes and silatranes. (1st September 2021) - Singh, Gurjaspreet; Priyanka; Sushma; Diksha; Mohit; Suman; Kaur, Jashan Deep; Saini, Anamika; Satija, Pinky
Abstract : This article represents the synthesis of 1, 2, 3 triazoles allied Schiff base functionalized silanes and silatranes. The silane 5a and silatrane 6a were investigated for their photophysical potential via absorption and emission spectroscopy and found selective for Sn(ii ). Abstract : Organosilicon chemistry is appraised as the trunk of coalescence and structural manoeuvres of moieties. Schiff base compounds are popular auxiliary scaffolds having vast applications in the fields of biological activities, organic synthesis, sensing, catalysis and agriculture. Here, in this article we have presented the synthesis, structural elucidation and photophysical aspects of 1, 2, 3-triazole allied Schiff base functionalized silanes (5a–5d ) and silatranes (6a–6d ). A two-step approach was followed to synthesize the desired products and the compounds were confirmed by NMR ( 1 H and 13 C) and mass spectrometry. The silane 5a and silatrane 6a were investigated by density functional theory and their photophysical potential via absorption and emission spectroscopy. The probes were found to be specific and selective only for Sn 2+ metal ions. The limit of detection values were found to be 0.86 × 10 −8 M and 0.58 × 10 −8 M for 5a & 6a, respectively, from absorption spectroscopy. The limit of detection values from emission spectroscopy were calculated as 1.3 × 10 −9 M and 0.64 × 10 −9 M for 5a & 6a, respectively. Furthermore, the high binding efficiency of Sn(ii ) with sensors 5a & 6a was confirmed by the high association constants ( K a ) from the linear calibration curves as 4.6 × 10 6 M −1 and 0.15 × 10 7 M −1, respectively, for 5a & 6a . The Stern–Volmer plot was explored to calculate the Stern–Volmer constants ( K sv ), which were found to be 21.66 × 10 7 M −1 and 30.39 × 10 7 M −1 . A Job's plot confirmed the 1 : 1 stoichiometric ratio of host:guest in both 5a & 6a .